THE PROTAGONIST IN KAVITA KANE'S NOVEL "KARNA'S WIFE: THE OUTCAST'S QUEEN" FACES SOCIO-PSYCHOLOGICAL CHALLENGES - AN ANALYTICAL INVESTIGATION - Vidhyarthini, S.N.; Bharathiraja, S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study analyses the socio-psychological challenges encountered by the protagonist in Kavita Kane's novel "Karna's Wife: The Outcast's Queen," exploring the factors contributing to the socio-psychological difficulties faced by marginalised individuals throughout the historical era portrayed in the book. This study aims to investigate the existing social circumstances during that period and evaluate their influence on causing psychological discomfort in the main character. The Freudian psychological perspective asserts that the source of psychological distress is located in the unconscious mind, while the Marxist perspective argues that it is grounded in the current material circumstances of social existence. The use of the Marxist literary critical approach is crucial for doing this research, as it allows for the analysis of the dialectical relationship between the human psyche and the prevailing social relations during that period. It is said that social discriminations can have negative effects on persons' socio-psychological well-being, and this was also the case for Karna.